Performance of Islamic Financial: A Qualitative Study In Improving The Regional Economy - Anton Priyo Nugroho (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
Islamic financial institutions offer resources that the community can employ to expand economic opportunities and strengthen the local economy. The primary competitive and productive force in the national economy is the regional economy. Because of this, the growth of micro, small, and medium-sized businesses must be the nation's top goal in terms of economic development. The purpose of this study is to demonstrate how Islamic financial institutions help local business owners achieve economic development. This kind of research is a literature review, using data sources found by using preset variable keywords to search Google Scholar. The role of financial institutions in the economy, including asset transfers, transactions, liquidity, and efficiency, is covered by the study's findings. The purpose of Islamic financial institutions is to advance and foster the integration of Islamic values, sharia, and customs into banking, finance, and associated industries